Bridging Cognitive Load and Self-Regulated Learning Research: A complementary approach to contemporary issues in educational research. (October 2017) - de Bruin, Anique B.H.; van Merriënboer, Jeroen J.G.
Abstract: The aim of this Introduction to the Special Issue 'Bridging Cognitive Load and Self-Regulated Learning Research' is to explore how cognitive load theory, which is particularly relevant for how learners deal with complex information, and self-regulated learning theory, which is particularly relevant for how learners use information to monitor and control their learning, can be combined into one joint research paradigm that is relevant for contemporary and future developments in education. The first two sections introduce cognitive load theory and self-regulated learning theory. The third section discusses the main similarities and differences between the theories, and describes how the cue-utilization framework can be used as the basis for a joint research paradigm. The main idea postulated is that new instructional methods should help learners identify diagnostic cues in available information that provide an accurate indication of where learners stand in relation to criterion task performance. Use of these diagnostic cues when monitoring learning will lead to better regulation of learning activities and of mental resources allocated, and thus to more efficient learning and higher learning outcomes. In the fourth section, the six studies and two commentaries presented in this special issue are positioned within this paradigm. In the fifth and final section, a common research agenda based on the joint CLT-SRL paradigm is sketched and its relevance for future developments is explained. The studies presented in this special issue and the two commentaries, which complete the Special Issue, should be seen as a very first step in executing this research agenda. Highlights: This introduction covers bridging cognitive load and self-regulated learning theory. Life-logging is a future issue in education profiting from bridging CLT and SRL. Designing cue prompts that predict mental effort and learning is a way forward. Cue prompts generate diagnostic cues learners use when judging effort and learning.